Determinants of coaches' intentions to provide different recommendations on sports nutrition to their athletes - Raphaëlle Jacob; Steven Couture; Benoît Lamarche; Véronique Provencher; Éliane Morissette; Pierre Valois; Claude Goulet; Vicky Drapeau (Taylor & Francis Group, 2019)
Background Coaches are considered as an important source of nutrition information by their athletes. However, their knowledge in this area is often insufficient for proper guidance and may lead to the dissemination of misinformation regarding sports nutrition. The aim of this study was to assess coaches' intentions as well as psychosocial determinants underlying their intentions to provide sports nutrition recommendations to their high school athletes. Methods Coaches (n = 47) completed a Web-based questionnaire based on the theory of planned behaviour, to assess their intentions to provide three different sports nutrition recommendations and their determinants. Multiple regression analyses were used to identify the variables that were most strongly related to the intentions. Results Forty-six, 44.7 and 91.9% of coaches had the intention to recommend a higher consumption of foods rich in carbohydrates, foods rich in proteins and an increase in hydration to their athletes, respectively. Subjective norm was the only significant determinant of coaches' intention to recommend a higher consumption of foods rich in carbohydrates (R 2 = 53.7%, β = 0.73 ± 0.12, P < 0.0001). Subjective norm and perceived behavioural control were significantly associated with coaches' intentions to recommend a higher consumption of foods rich in proteins (R 2 = 25.9%, β = 0.50 ± 0.16, P = 0.002 and R 2 = 17.2%, β = 0.39 ± 0.17, P = 0.01, respectively) and an increase in hydration (R 2 = 26.8%, β = 0.38 ± 0.13, P = 0.001 and R 2 = 46.3%, β = 0.58 ± 0.11, P < 0.0001, respectively). Conclusions The results of this study suggest that subjective norm and perceived behavioural control represent important determinants of coaches' intentions to provide recommendations on sports nutrition. These findings should be considered in future interventions aimed at facilitating proper general sports nutrition recommendations provided by coaches to their athletes.